Pengaruh Terapi Slow Deep Breathing dengan Kombinasi Aromatherapy Mawar Terhadap Tekanan Darah pada Ibu Hamil dengan Hipertensi - Ade Reza Dwi Friskia; Rinda Intan Sari; Sri Hartini Mardi Asih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
A relaxation technique known as slow deep therapy is a non-pharmaceutical method for treating high blood pressure. The same matter goes for rose aromatherapy. The research attempts to relieve pregnant women’s hypertension using rose aromatherapy. This quasi-experimental research used a cross-sectional approach with one group pretest-posttest design. The respondents were 35 individuals taken with a total sampling technique. The results showed that 31 respondents (88.6%) were aged between 20 and 35 years, 20 of them were multigravida (57.1%), and 33 respondents had no concomitant disease (94.3%). Before the implementation of combined slow-deep breathing and rose aromatherapy, the mean score of pre-systolic blood pressure was 138.66 mmHg while the mean of pre-diastolic pressure was 86.69 mmHg. After the intervention, the pre-systolic blood pressure mean was 130.80 mmHg while the pre-diastolic blood pressure was 85.06 mmHg. The Wilcoxon statistic test obtained a p-value of 0.000 lower than 0.05, This means that there is an effect of Slow Deep Breathing therapy combined with Rose Aromatherapy on the blood pressure of pregnant women with hypertension at the Semarang City Health Center. It is hoped that the results of this research can be used as another alternative to reducing blood pressure in pregnant women with hypertension.